2016
DOI: 10.1016/j.puhe.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The experience of potentially vulnerable people during cold weather: implications for policy and practice

Abstract: ObjectivesTo examine the experience of potentially vulnerable people during cold weather to inform interventions aimed at improving wellbeing. Study designQualitative study. MethodsTelephone interviews with 35 individuals who could be considered to be potentially vulnerable during cold weather. Individuals were interviewed on two occasions during the winter of 2012-13, one or two days after a level 3 cold weather alert as defined by the CWP had been issued. ResultsParticipants were largely unaware of the healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Variations in the distributions of the above health, demographic, socio-economic and built-environment characteristics are likely to explain most differences in cold risk observed between UK regions. The most recent UK evidence on regional variations in cold risk are provided by an evaluation of the Public Health England Cold Weather Plan, [ 47 , 48 ] as part of which epidemiologic assessment of retrospective data was conducted [ 29 ]. Adverse cold-related health impacts were observed in all regions, with the North East, North West and London experiencing the greatest relative increase in mortality.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in the distributions of the above health, demographic, socio-economic and built-environment characteristics are likely to explain most differences in cold risk observed between UK regions. The most recent UK evidence on regional variations in cold risk are provided by an evaluation of the Public Health England Cold Weather Plan, [ 47 , 48 ] as part of which epidemiologic assessment of retrospective data was conducted [ 29 ]. Adverse cold-related health impacts were observed in all regions, with the North East, North West and London experiencing the greatest relative increase in mortality.…”
Section: Reviewmentioning
confidence: 99%
“…The plan provides advice for individuals, communities and agencies on how to prepare for and respond to severe cold weather, and initiates acute actions by health and social care professionals and other community organisations to strengthen the protection and support of vulnerable individuals when cold weather is forecast. As well as a recent process evaluation of this plan, [ 29 , 47 , 48 ] and possible future changes to the alert system employed, [ 74 ] further qualitative information has led to updates to the plan which the authors describe as an example of pragmatic evidence-based policy making [ 75 ]. To date, however, there is little quantitative evidence on the effectiveness of such plans either from England or elsewhere in the world.…”
Section: Reviewmentioning
confidence: 99%
“…Living in cold and damp environments is associated with health risks such as cardiovascular disease, asthma and respiratory problems. In addition, social isolation and inequality are further promoted when these conditions are present in social housing, because occupants are very often unable to afford the cost of keeping dwellings adequately warm (Jones and Mays, 2016). Thermal comfort is one of the most immediate and direct aspects that influence occupants of the built environment.…”
Section: Introductionmentioning
confidence: 99%
“…Before this study perception of risk has not emerged as an important thread in understanding people with dementia's approach to warmth and safety at home in winter. In qualitative studies with older people without dementia, it has been found that people have an incomplete understanding of the health effects and risk of living in a cold environment (Chard and Walker, 2016;Jones and Mays, 2016;O'Neil, Jinks and Squire, 2006), something that was seen in this study. However, older people without dementia have not been identified as having the same problems perceiving risks in day-to-day warmth and safety that emerged in this study.…”
Section: Not Seeing the Risksmentioning
confidence: 58%
“…The literature search was conducted in November 2015 and was updated in May 2017. The update to the literature review added three items to the literature review (Chard and Walker, 2016;Gray et al, 2015;Jones and Mays, 2016). They did not materially change the focus of the review and so were integrated into the existing literature review.…”
Section: Key (Home or House Or Alone Or Accommodation)mentioning
confidence: 99%